An Experimental Study on the Healing Effect of Water to Traditional Sudanese Liquor (Aragi)-induced Stomach Peptic Ulcers - Entisar Kuku Yousif; Howeida Abdullah Mustafa; Alkhair Abd Almahmoud Idris (Molecular and Cellular Biomedical Sciences, 2022)
Background: Peptic ulcer is one of the most common gastrointestinal tract diseases which affect the stomach. This study aimed to determine the effect of aragi on the adult rats' stomach and investigate the effect of water as a therapeutic agent on aragi-induced ulcerations.Materials and methods: Thirty-five adult Wistar albino rats were used in this experimental study. Five rats were sacrificed on day 0, 5 rats were used as a control group, and 25 rats were treated with aragi. On day 15, all rats in the control group and five aragi-treated rats were sacrificed for histological examination of the stomachs. The remaining 20 rats were stopped from aragi intake and 10 of them were treated with water for 15 days. After 15 day, all rats were sacrificed for histopathological examination of their stomachs. Stomach tissues were stained using hematoxylin and eosin (H&E) and documented under a microscope.Results: Our research showed that aragi-treated rats had different severity of peptic ulcers after 15 days of continuous aragi intake, while the control group showed normal stomach histology. Nine out of 10 rats treated by water after aragi treatment also showed normal stomach histology.Conclusion: Aragi is a causative agent for peptic ulcer and water can be used as potential natural therapy for treating ulcerative stomach.Keywords: aragi, water, stomach, peptic ulcer